Hubungan Partisipasi Suami dan Sosial Budaya dengan Pemilihan Alat Kontrasepsi IUD pada Pasangan Usia Subur di Wilayah Kerja Puskesmas Barambai Tahun 2025 - Siti Rahayu; Rubiati Hipni; Fitria Jannatul Laili; Rusmilawaty Rusmilawaty (JURNAL KEBIDANAN BESTARI, 2025)
Introduction: The choice of contraception is a very important aspect in reproductive health, especially for couples of childbearing age in South Kalimantan, especially in Barito Kuala Regency, the use of IUD as a Barito Kuala Regency shows that only 15% couples of childbearing age choice IUD as a contraceptive method. Objective: To determine the relationship between husband participation and socio-culture on the choice of IUD contraception in methods among couples of reproductive age in the working area of the Barambai Health Center in 2025. Methods: This research was a correlation analytical study using a cross sectional approach. The sampling technique used was a Cluster Randonm Sampling with 97 respondents who met the inclusion criteria. Data were analyzed using the Chi Square test with a significance value of 0,05. Results: Out of the total respondent, 38 (39,2%) chose IUD contraception, 41 (42,3%) reported that theeir husbands were involved in the decidion-making process, and 34 (35,1%) were influenced by sosio-cultural factors. The chi square test results showed a significant relationship between husband participant (p 0,000) and the choice IUD contraception, and showed that there was a relationship between socio-culture (p 0,020), and the choice IUD contraception Conclusion: There is relationship between husbands participant and socio-cuture and the choice of IUD contraception in fertie coupes in the Barambai Health Center in 2025 Keywords: IUD, contraception, husband participant , socio-culture.